2000
DOI: 10.1097/00006676-200010000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Calmodulin and Protein Kinase C in Cholecystokinin Release by Bombesin from STC-1 Cells

Abstract: The mouse intestinal neuroendocrine tumor cell line STC-1 secretes cholecystokinin (CCK) and other hormones. We investigated the role of Ca2+, calmodulin (CaM), and protein kinase C (PKC) in the regulation of CCK release from STC-1 cells. Phorbol 12-myristate 13-acetate (TPA) significantly stimulated CCK release. Staurosporine significantly inhibited CCK release from STC-1 cells stimulated by TPA in a dose-dependent manner. The absence of extracellular calcium completely inhibited CCK release from TPA-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…While the involvement of fatty acid transporters in the glucoregulatory effects of intraduodenal lipids has not been tested, a likely role of fatty acid transporter cluster of differentiation 36 (CD36) is presented given that CD36 À/À mice exhibit a reduced satiety response as well as reduced CCK release in response to intestinal lipids Sundaresan et al, 2013) ( Figure 1). Furthermore, the glucose-lowering effect of LCFAs is mediated by the activation of duodenal protein kinase C (PKC)-d, which is expressed in rodent and human duodenal mucosa (Breen et al, 2011;Kokorovic et al, 2011), consistent with studies reporting that PKC-d mediates LCFA-induced CCK secretion from STC-1 cells (Chang et al, 2000;Takahashi et al, 2000). Although the downstream signaling events of PKC-d remain unclear, this glucose-lowering LCFA/LCFACoA/PKC-d axis requires activation of duodenal CCK-1 receptors (CCK-1R) (Breen et al, 2011;Cheung et al, 2009).…”
Section: Intestinal Nutrient Sensingsupporting
confidence: 73%
“…While the involvement of fatty acid transporters in the glucoregulatory effects of intraduodenal lipids has not been tested, a likely role of fatty acid transporter cluster of differentiation 36 (CD36) is presented given that CD36 À/À mice exhibit a reduced satiety response as well as reduced CCK release in response to intestinal lipids Sundaresan et al, 2013) ( Figure 1). Furthermore, the glucose-lowering effect of LCFAs is mediated by the activation of duodenal protein kinase C (PKC)-d, which is expressed in rodent and human duodenal mucosa (Breen et al, 2011;Kokorovic et al, 2011), consistent with studies reporting that PKC-d mediates LCFA-induced CCK secretion from STC-1 cells (Chang et al, 2000;Takahashi et al, 2000). Although the downstream signaling events of PKC-d remain unclear, this glucose-lowering LCFA/LCFACoA/PKC-d axis requires activation of duodenal CCK-1 receptors (CCK-1R) (Breen et al, 2011;Cheung et al, 2009).…”
Section: Intestinal Nutrient Sensingsupporting
confidence: 73%
“…Moore et al (38) reported that stimulation of G cells with BBS resulted in the translocation of PKC-␥ from a predominantly intracellular location to the plasma membrane. Another study, using the STC-1 cell line, demonstrated that CCK secretion in response to BBS involves MAPK activation through a PKC-dependent mechanism (50). We found that BBS-mediated NT secretion in the BON/ GRP-R cell line, similar to PMA stimulation, was inhibited by using the PKC inhibitors, including the specific PKC-␦ inhibitor rottlerin.…”
Section: Discussionmentioning
confidence: 59%
“…The conventional isoforms require both Ca 2ϩ and diacylglycerol (DAG), novel isoforms are Ca 2ϩ independent, and atypical isoforms are Ca 2ϩ independent and DAG or phorbol ester resistant (39,41). In endocrine cells, particularly in the pancreas and thyroid, PKC isoforms have been detected and linked to the regulation of hormone secretion (9,16,20,22,23,35,42,49,50,57). On activation, PKC isoforms translocate to new cellular sites, including the plasma membrane, cytoskeletal elements, and the nucleus, as well as other subcellular compartments (39,41).…”
mentioning
confidence: 99%
“…The biologically active DBI fragment DBI (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) induces Ca 2ϩ oscillations and CCK secretion in STC-1 cells (151). In addition to luminal factors, neuropeptide bombesin (101,131,136), ␤-adrenergic receptor agonist (127), GABA (44,54), and orexins (69) could all stimulate I cell CCK secretion. Both radioligand binding studies and Northern blot analyses suggested the presence of bombesin-like receptors in CCK cells (131).…”
Section: Gut Cck-secreting Cellmentioning
confidence: 99%
“…Both radioligand binding studies and Northern blot analyses suggested the presence of bombesin-like receptors in CCK cells (131). Bombesin-stimulated CCK secretion from STC-1 cells was PKC dependent and involved the MAPK pathway (101) and calmodulin (136). Liddle and colleagues (127) demonstrated the presence of ␤-adrenergic receptors in STC-1 cells, the stimulation of which led to cAMP production and CCK release (127).…”
Section: Gut Cck-secreting Cellmentioning
confidence: 99%